Pelatihan Kerajinan Kertas Kokoru untuk Meningkatkan Ketrampilan dan Kreatifitas Guru PAUD di Desa Kalisalak - Nafsah, Banatinnasi; Hidayat, Arif (J-PGMI: Jurnal Pendidikan Guru MI, 2023)
This activity is motivated by the need for skills and creativity needed by an early childhood teacher. Teacher teaching skills are needed in early childhood, especially fine motor skills in children aged 4-6 years. The creativity of a PAUD teacher is an important factor in the learning process. Therefore, it is necessary to carry out the training and skills of an PAUD teacher, one of which is the kokoru craft. Kokoru paper craft is one of the learning media that can train fine motor skills for early childhood. In addition, kokoru paper can also train the creativity of a PAUD teacher. The purpose of this training is to train the skills and creativity of PAUD teachers so that teachers can add variety in teaching activities. So that it will create fun learning and can also improve the quality of early childhood. The method used is Demonstration Method. The subjects of the training were PAUD Kalisalak teachers, Kebasen sub-district, Banyumas district. The activity begins with a brief explanation of how to roll kokoru paper properly so that it can create a form of cartoon characters, fruit, animals, etc. and then the teacher practices directly according to the imagination.